A Critical Study of Leadership Characteristics of the Prophet Yusuf () through the Surah Yusuf - ณรงค์รักษาเขต อิบรอฮีม (Al-HIKMAH Journal, 2018)
This article is a documentary study which critically examines the story of the Prophet Yusuf (u) one of the most detailed and fascinating stories revealed as the twelfth Surah of the holy Quran. It involves both human weaknesses such as jealousy, hatred, pride, passion, and deception, as well as noble qualities such as patience, loyalty, bravery, nobility, and compassion. This study mainly aims to study administrative capabilities of the Prophet Yusuf (u). Besides that the study also aims to analyze some critical questions. For instance, was the Prophet Yusuf (u) born as a leader and administrator?, why did the Prophet Yusuf confidentially make a proposal to pose himself as an administrator over the land of Egypt which would face with severe drought?, why did the Prophet Yusuf (u) utter words of praise for himself ?, does not the Qur’an say that one should not praise himself?, why did the Prophet Yusuf (u) cooperate with an infidel government ?, is it not the case that this is forbidden in the Qur’an?, why did the king strongly believe that the Prophet Yusuf could work effectively in his administration?. Result of the study shows that the Prophet Yusuf (u) is an outstanding and exceptional administrator who possesses high administrative capabilities and qualities of leadership